The Role of Fantasy and Magical Realism in Confronting Trauma in Rajiv Joseph’s Bengal Tiger at the Baghdad Zoo - Mutashar, Hussein Zaboon (Journal of Innovation in Education and Social Research, 2025)
This paper investigates how Rajiv Joseph’s play titled Bengal Tiger caged in Baghdad Zoo (2010) deals with trauma through the application of magical realism and literary fantasy, examines how these literary items expose the case of confrontation and healing in the play. By using mystical aspect and magical realism, Joseph, highlights the intricacies of emotional landscape, produced by memory, loss, and human intimacy. Exposing the lines between reality and imagination, the author indicates trauma as a story in evolution that can hardly be contained by the normal structures of space and time. This study presents how joseph applies magical realism and fantasy to cover the realism in describing trauma and offers a creative background for describing the ineffable. Supported by trauma theory, literary analysis and aspects of theater studies in a vigorously interdisplinary approach. The paper critically assesses the extent to which such practices allow the confrontation of trauma in an excellent and impressively invested ways, simultaneously by the actors themselves and the audiences.